Unravelling the Link between Math Anxiety and Math Performance of Grade 6 Pupils - Edmalyn Galano; Patricia Mae Calica; Jae Anne Nisperos; Helen Marie Zaragoza; Lailanie Soriano; Oscar Jr. Ancheta (Diversitas Journal, 2025)
This study aimed to assess the relevance of math anxiety in relation to academic performance among 56 Grade 6 pupils at DMMMSU-MLUC LES. Many students struggle in mathematics due to conceptual difficulties and negative perceptions, which increase anxiety, self-doubt, and fear of failure—ultimately hindering academic achievement. Coping strategies such as building self-confidence, practicing problem-solving, and seeking support are essential in managing anxiety. Personalized interventions like collaborative learning, hands-on activities, and cognitive strategies help foster engagement and reduce anxiety. Support systems involving teachers, parents, and peers further influence students’ motivation and resilience.A mixed-methods design was employed, combining quantitative surveys and qualitative interviews with 20 selected students. Academic records from the 1st and 2nd grading periods revealed a slight improvement in math grades, from 87.96 to 88.88, with an overall mean of 88.42. The math anxiety survey produced a mean score of 3.30, indicating a moderate level of anxiety. Correlation analysis showed a moderate negative relationship between anxiety and performance (r = -0.58, p = 0.049), suggesting that higher anxiety levels are associated with lower academic achievement.In response to these findings, the researchers developed an intervention program titled Math3matics: Empower, Excel, Exceed. The program features confidence-building exercises, guided problem-solving, peer collaboration, and interactive activities. It promotes teacher-guided instruction and student-centered learning approaches to enhance mathematical competence, reduce anxiety, and foster a growth mindset. The results emphasize the importance of addressing emotional, instructional, and social factors to improve students’ experiences and outcomes in mathematics.